Application of high temperature anti-slag graphite emulsion spray in stainless steel strip

By spraying high-temperature anti-sticking graphite emulsion on the stainless steel plate tape, and using modified graphene oxide and other components, the problem of bonding iron powder during storage of the stainless steel plate tape is solved, significantly improving its corrosion resistance and service life.

CN117025040BActive Publication Date: 2025-04-01GKN (BAZHOU) METAL POWDER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311039750.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-04-01
Estimated Expiration
2043-08-17

AI Technical Summary

Technical Problem

Stainless steel plate tape is prone to bond iron powder during storage, resulting in rust on the surface, reducing corrosion resistance and affecting service life.

Method used

High-temperature anti-stick slag graphite emulsion spray is used, and the combination of modified graphene oxide, resin, surfactant and other components is sprayed onto stainless steel plate strips to improve its corrosion resistance.

Benefits of technology

Effectively isolate iron powder and dust in the environment, reduce adhesion, improve the corrosion resistance and service life of stainless steel strips, and reduce the cost of use and environmental protection risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel strips, and proposes an application of high-temperature anti-sticking slag graphite emulsion spray in stainless steel strips, wherein the graphite emulsion comprises the following components by weight: 20-25 parts of modified graphene oxide, 5-7 parts of resin, 0.5-1.5 parts of surfactant, and 65-70 parts of water; the modified graphene is obtained by modifying graphene oxide with triethylenetetramine and isopropyl p-aminobenzoate. Through the above technical scheme, the problem of poor corrosion resistance of stainless steel strips in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel strips, and in particular to application of high-temperature anti-slag graphite emulsion spray in stainless steel strips. Background Art

[0002] Stainless steel plates have the characteristics of great strength and hardness, and are not easily deformed during construction and use. They have become the first choice for decoration projects and have been widely used in decoration, industry, automobiles and other fields.

[0003] In order to ensure that the stainless steel plate has good corrosion resistance, the surface of the stainless steel plate needs to be kept clean and pollution-free. However, during the storage of the stainless steel plate, some iron powder will adhere to the surface of the stainless steel plate, which will not only cause rust on the surface of the stainless steel plate, reducing the anti-corrosion performance of the stainless steel plate, but also harm the oxide protective film of the stainless steel plate, ultimately reducing the corrosion resistance of the prepared stainless steel plate and affecting its service life. Summary of the invention

[0004] The invention proposes an application of high-temperature anti-sticking slag graphite emulsion spray in stainless steel strips, which solves the problem of poor corrosion resistance of stainless steel strips in the related art.

[0005] The technical solution of the present invention is as follows:

[0006] A high-temperature anti-sticking slag graphite emulsion comprises the following components in parts by weight: 20-25 parts of modified graphene oxide, 5-7 parts of resin, 0.5-1.5 parts of surfactant, and 65-70 parts of water; the modified graphene is obtained by modifying graphene oxide with triethylenetetramine and isopropyl p-aminobenzoate.

[0007] As a further technical solution, the resin consists of water-based acrylic resin and water-based epoxy resin.

[0008] As a further technical solution, the mass ratio of the water-based acrylic resin to the water-based epoxy resin is 1:1.

[0009] As a further technical solution, the surfactant includes one or more of sodium dodecylbenzene sulfonate, stearic acid and alkylphenol polyoxyethylene ether.

[0010] As a further technical solution, the preparation method of the modified graphite particles is:

[0011] S1. Mixing graphene oxide and N,N-dimethylformamide to obtain a mixture A;

[0012] S2. Add triethylenetetramine, isopropyl p-aminobenzoate and dicyclohexylcarbocyanine to mixture A for reaction to obtain mixture B.

[0013] S3. Add ethanol to the mixture B, let it stand, remove the upper clear liquid, take the lower precipitate, wash and dry it, and obtain modified graphene oxide.

[0014] As a further technical solution, S3 is to add anhydrous ethanol to mixture B, let it stand for 12 hours, remove the upper clear liquid, filter the lower precipitate with a polytetrafluoroethylene membrane, and wash the precipitate with ethanol, and dry the washed precipitate at 70°C to obtain modified graphene oxide.

[0015] As a further technical solution, the mass ratio of graphene oxide to N,N-dimethylformamide in S1 is 1:30-40.

[0016] As a further technical solution, the mixing in S1 is ultrasonic mixing, the ultrasonic power is 300-400W, and the ultrasonic time is 2-3h.

[0017] As a further technical solution, the mass ratio of the triethylenetetramine and isopropyl p-aminobenzoate to graphene oxide is 8-10:1.

[0018] As a further technical solution, the mass ratio of triethylenetetramine to isopropyl p-aminobenzoate is 1-2:1.

[0019] As a further technical solution, the mass ratio of triethylenetetramine to isopropyl p-aminobenzoate is 1.5:1.

[0020] As a further technical solution, the reaction temperature in S2 is 110-130° C., and the reaction time is 36-48 h.

[0021] The present invention also includes the application of high-temperature anti-sticking slag graphite emulsion spray in stainless steel plates and strips, which is characterized in that the cold-rolled stainless steel strips are sprayed with a diluted graphite solution, and then annealed, electrolyzed, and pickled to obtain a stainless steel strip semi-finished product, and then the diluted graphite emulsion is used to spray the stainless steel strip semi-finished product in the form of a spray to obtain a stainless steel strip sprayed with graphite emulsion.

[0022] As a further technical solution, the graphite solution consists of graphite and water.

[0023] As a further technical solution, the mass ratio of graphite to water is 3:1.

[0024] The working principle and beneficial effects of the present invention are:

[0025] 1. The present invention modifies graphene oxide in graphite emulsion by using triethylenetetramine and isopropyl p-aminobenzoate, and the obtained modified graphene oxide has improved water resistance. Spraying the modified graphene oxide onto a stainless steel plate can further improve the corrosion resistance of the stainless steel plate.

[0026] 2. In the present invention, by limiting the mass ratio of triethylenetetramine to isopropyl p-aminobenzoate to 2-3:1, the water resistance of the stainless steel strip can be improved, thereby further improving the corrosion resistance of the stainless steel strip.

[0027] 3. After the high-temperature anti-sticking slag graphite emulsion is sprayed onto the stainless steel strip in the form of a spray, the stainless steel strip will isolate the iron powder, dust and other substances in the environment during storage, reduce the adhesion of impurities such as iron powder and dust on the surface of the stainless steel strip, and increase the service life of the stainless steel strip.

[0028] 4. The present invention sprays graphite solution on the stainless steel sheet before annealing, and the surface of the prepared stainless steel sheet is smooth and clean without impurities adhering. The applicant analyzed that it may be the sprayed graphite solution. The graphite in the graphite solution can cover the stainless steel sheet within a certain period of time, thereby isolating the stainless steel sheet from the iron powder, so that the iron powder will not adhere to the surface of the stainless steel sheet, thereby making the surface of the prepared stainless steel sheet smooth and clean.

[0029] In addition, the graphite solution used in the present invention has the following advantages compared with conventional kerosene fumigation:

[0030] (1) From the perspective of cost analysis, the cost of the graphite solution used in the present invention is lower than that of traditional kerosene fumigation, saving 0.4 yuan per ton;

[0031] (2) From the analysis of the use effect, the graphite solution spraying process used in the present invention is stable, and the graphite can evenly cover the surface of the stainless steel strip within a certain period of time, and the surface of the stainless steel strip is smooth and clean. However, in the traditional kerosene fumigation, the kerosene flame is not easy to control, the operation is difficult, and the kerosene fumigation is uneven, and a large amount of iron powder is still adhered to the surface of the stainless steel strip;

[0032] (3) From the perspective of environmental protection, the graphite solution used in the present invention does not cause any pollution to the environment, while the kerosene smoke generated by kerosene fumigation not only pollutes the environment, but also requires the use of dust removal equipment to eliminate the pollution caused by kerosene fumigation to the environment;

[0033] (4) From the perspective of safety and convenience, kerosene is a flammable liquid and poses a fire hazard. It needs to be stored outside the workshop as required, which makes it inconvenient for workers to retrieve the material. However, graphite solution can be placed inside the workshop, and workers can retrieve the material at any time as needed. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the following embodiments and comparative examples:

[0036] Graphene oxide, product number BY-20040, was purchased from Qinghe County Benyu Metal Materials Co., Ltd.;

[0037] Water-based acrylic resin: model SK6462Y, purchased from Shanghai Shuai Ke Chemical Co., Ltd.;

[0038] Waterborne epoxy resin: Model S-990, purchased from Qingdao Wanjia Huixin Surface Material Technology Co., Ltd.

[0039] Example 1

[0040] 20 parts of modified graphene oxide, 2.5 parts of water-based acrylic resin, 2.5 parts of water-based epoxy resin, 0.5 parts of sodium dodecylbenzene sulfonate and 65 parts of water are uniformly mixed to obtain a graphite emulsion;

[0041] The preparation method of modified graphene oxide is as follows:

[0042] S1, treating 30 parts of graphene oxide and 900 parts of N,N-dimethylformamide by ultrasonic treatment at a power of 300 W for 3 h to obtain a mixture A;

[0043] S2, adding 144 parts of triethylenetetramine, 96 parts of isopropyl p-aminobenzoate and 10 parts of dicyclohexylcarbocyanine to mixture A at 110° C., reacting for 48 hours, to obtain mixture B;

[0044] S3. Add 150 mL of anhydrous ethanol, let stand for 12 hours, remove the upper clear liquid, filter the lower precipitate with a polytetrafluoroethylene membrane, and wash the precipitate with ethanol. Dry the washed precipitate at 70° C. to obtain modified graphene oxide.

[0045] Example 2

[0046] 22 parts of modified graphene oxide, 3 parts of water-based acrylic resin, 3 parts of water-based epoxy resin, 1 part of stearic acid, and 68 parts of water are uniformly mixed to obtain a graphite emulsion;

[0047] The preparation method of modified graphene oxide is as follows:

[0048] S1, treating 30 parts of graphene oxide and 1000 parts of N,N-dimethylformamide by ultrasonic treatment at a power of 350 W for 2.5 h to obtain a mixture A;

[0049] S2, adding 168 parts of triethylenetetramine, 112 parts of isopropyl p-aminobenzoate and 10 parts of dicyclohexylcarbocyanine to mixture A at 120° C., reacting for 40 hours, to obtain mixture B;

[0050] S3. Add 150 mL of anhydrous ethanol, let stand for 12 hours, remove the upper clear liquid, filter the lower precipitate with a polytetrafluoroethylene membrane, and wash the precipitate with ethanol. Dry the washed precipitate at 70° C. to obtain modified graphene oxide.

[0051] Example 3

[0052] 25 parts of modified graphene oxide, 3.5 parts of water-based acrylic resin, 3.5 parts of water-based epoxy resin, 1.5 parts of alkylphenol polyoxyethylene ether, and 70 parts of water are uniformly mixed to obtain a graphite emulsion;

[0053] The preparation method of modified graphene oxide is as follows:

[0054] S1, treating 30 parts of graphene oxide and 1200 parts of N,N-dimethylformamide by ultrasonic treatment at a power of 400 W for 2 h to obtain a mixture A;

[0055] S2, adding 180 parts of triethylenetetramine, 120 parts of isopropyl p-aminobenzoate and 10 parts of dicyclohexylcarbocyanine to mixture A at 130° C., reacting for 36 hours to obtain mixture B;

[0056] S3. Add 150 mL of anhydrous ethanol, let stand for 12 hours, remove the upper clear liquid, filter the lower precipitate with a polytetrafluoroethylene membrane, and wash the precipitate with ethanol. Dry the washed precipitate at 70° C. to obtain modified graphene oxide.

[0057] Example 4

[0058] Compared with Example 1, the difference of Example 4 is that 120 parts of triethylenetetramine and 120 parts of isopropyl p-aminobenzoate are used.

[0059] Example 5

[0060] Compared with Example 1, the difference of Example 5 is that 160 parts of triethylenetetramine and 80 parts of isopropyl p-aminobenzoate are used.

[0061] Comparative Example 1

[0062] Compared with Example 1, isopropyl p-aminobenzoate is not added in Comparative Example 1, and the other parts are the same as those in Example 1.

[0063] Comparative Example 2

[0064] Compared with Example 1, Comparative Example 2 does not add triethylenetetramine, and the other parts are the same as Example 1.

[0065] Comparative Example 3

[0066] Compared with Example 1, in Comparative Example 3, isopropyl p-aminobenzoate is replaced with an equal amount of ethylenediamine, and the rest is the same as Example 1.

[0067] Test example

[0068] The corrosion resistance of the graphite emulsions prepared in Examples 1-5 and Comparative Examples 1-3 to stainless steel strips was determined by the following method:

[0069] The graphite emulsion was diluted 15 times with water and then loaded into a graphite emulsion atomizer. After spraying the semi-finished stainless steel strip with 0.5Mpa compressed air at a spraying speed of 45mL / s, the semi-finished stainless steel strip was dried at 80°C to obtain a stainless steel strip sprayed with graphite emulsion.

[0070] The semi-finished stainless steel strip is obtained by spraying a diluted graphite solution on the cold-rolled stainless steel strip, and then annealing, electrolysis and pickling. The dilution multiple of the graphite solution is 12 times. The graphite solution consists of graphite and water, and the mass ratio of graphite to water is 1:3. The spraying parameters of the graphite solution are the same as those of the graphite emulsion.

[0071] Corrosion resistance test: The stainless steel strip sprayed with graphite emulsion was immersed in 25℃, 0.5mol / L hydrochloric acid solution for 10 days, and a control group was set up to measure the weight of the sample before and after immersion, and the weight loss was calculated, wherein the control group was the stainless steel strip not sprayed with graphite emulsion;

[0072] The measurement results are shown in Table 1.

[0073] Table 1 Determination results of corrosion resistance of stainless steel strips

[0074]

[0075] Compared with Example 1, Example 4-5 changes the mass ratio of triethylenetetramine and isopropyl p-aminobenzoate. As a result, the graphite emulsion prepared in Example 4-5 has a greater weight loss when sprayed on a stainless steel plate than in Example 1, indicating that when the mass ratio of triethylenetetramine and isopropyl p-aminobenzoate is 1.5:1, the prepared graphite emulsion sprayed on a stainless steel plate can further improve the corrosion resistance of the stainless steel plate.

[0076] Compared with Example 1, Comparative Example 1 does not add isopropyl p-aminobenzoate, Comparative Example 2 does not add triethylenetetramine, and Comparative Example 3 replaces isopropyl p-aminobenzoate with an equal amount of ethylenediamine. As a result, after the graphite emulsions prepared in Comparative Examples 1-3 are sprayed on the stainless steel plates and strips, the weight loss is greater than that of Example 1, indicating that the present invention jointly modifies graphene oxide by isopropyl p-aminobenzoate and triethylenetetramine, and the obtained modified graphene oxide is added to the graphite emulsion, and the graphite emulsion is sprayed on the stainless steel plates and strips, thereby improving the corrosion resistance of the stainless steel plates and strips.

[0077] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature anti-slag graphite emulsion, characterized in that: The invention comprises the following components in parts by weight: 20-25 parts of modified graphene oxide, 5-7 parts of resin, 0.5-1.5 parts of surfactant, and 65-70 parts of water; the modified graphene oxide is obtained by modifying graphene oxide with triethylenetetramine and isopropyl p-aminobenzoate; The preparation method of the modified graphene oxide is: S1. Mixing graphene oxide and N,N-dimethylformamide to obtain a mixture A; S2, adding triethylenetetramine, isopropyl p-aminobenzoate and dicyclohexylcarbocyanine to the mixture A for reaction to obtain a mixture B; S3, adding ethanol to the mixture B, after standing, removing the upper clear liquid, taking the lower precipitate, washing and drying, to obtain modified graphene oxide; The mass ratio of graphene oxide to N,N-dimethylformamide in S1 is 1:30-40; The mass ratio of the triethylenetetramine and isopropyl p-aminobenzoate to graphene oxide is 8-10:1; The mass ratio of triethylenetetramine to isopropyl p-aminobenzoate is 1.5:

1.

2. The high temperature anti-slag graphite emulsion according to claim 1, characterized in that: The resin consists of water-based acrylic resin and water-based epoxy resin.

3. The high temperature anti-slag graphite emulsion according to claim 1, characterized in that: The surfactant includes one or more of sodium dodecylbenzene sulfonate, stearic acid and alkylphenol polyoxyethylene ether.

4. The high temperature anti-slag graphite emulsion according to claim 1, characterized in that: The mixing in S1 is ultrasonic mixing, the ultrasonic power is 300-400W, and the ultrasonic time is 2-3h.

5. The high temperature anti-slag graphite emulsion according to claim 1, characterized in that: The reaction temperature in S2 is 110-130° C., and the reaction time is 36-48 h.

6. Application of high temperature anti-slag graphite emulsion in stainless steel strip, characterized in that: The cold-rolled stainless steel strip is sprayed with a diluted graphite solution, and then annealed, electrolyzed, and pickled to obtain a stainless steel strip semi-finished product. The diluted graphite emulsion according to any one of claims 1 to 5 is then sprayed on the stainless steel strip semi-finished product in the form of a spray to obtain a stainless steel strip sprayed with graphite emulsion.

Citation Information

Patent Citations

  • Alkali-resistant waterproof glass wool board

    CN108892417A

  • Modified graphene oxide, modified graphene, and modified graphene epoxy resin dispersion liquid

    CN109666259A

  • Modified graphene oxide aqueous antibacterial anticorrosive coating material and preparation method therefor

    CN110423533A